Meritocracy in the Selection of Senior Physical Education Managers in the Ministry of Education - Sadeghi Niyarki, Anahita; Nasiri Farsani, Mokhtar; Naderi Nasab, Mehdi (Journal of Foresight and Health Governance, 2026)
The objective of this study was to identify the factors affecting the merit-based selection of senior physical education managers in the national Ministry of Education. The present study was mixed-methods research (qualitative–quantitative) with an exploratory approach. The statistical population in the qualitative phase consisted of all experts in the research field (senior physical education managers of the Ministry of Education, faculty members familiar with the research literature, and specialists), while the quantitative phase included physical education managers and teachers in metropolitan areas of the country. The statistical sample in the qualitative phase consisted of 18 experts selected until theoretical saturation was achieved using purposive theoretical sampling and snowball sampling techniques. In the quantitative phase, considering that 5 to 10 samples were required for each item, a total of 384 individuals constituted the statistical sample. The data collection instruments included a semi-structured interview in the qualitative phase and a researcher-made questionnaire in the quantitative phase. Content validity was assessed based on expert opinions, and construct validity (exploratory and confirmatory factor analyses), composite reliability indices, Cronbach’s alpha, divergent and convergent validity, and structural equation modeling were employed. The model fit index was reported as GOF = 0.43. Finally, eight factors were identified: merit-oriented governance, professional ethics in power, transformational leadership in physical education, structural justice in access to opportunities, commitment to educational–health missions, professional autonomy in decision-making, intelligent resource management, and the organizational–cultural identity of managers. Therefore, the development and implementation of a “transparent system for managerial evaluation and appointment” based on objective merit indicators (such as professional competence, ethical commitment, and resource management capability), along with continuous supervision by independent monitoring bodies to prevent the influence of informal networks, is recommended.